Une perspective située pour penser l’appropriation des espaces de travail « par activités » - Chiara Lai; Maria Ianeva; Marc-Éric Bobillier Chaumon; Audrey Abitan (Activités)
In recent years, there has been growing interest in activity-based workspaces, that is to say offices with unassigned desks that offer a variety of workstations. These office solutions are expected to provide facilities that support the worker’s ongoing activity. In this context, our study seeks to address how activity-based workspaces and their functional characteristics are appropriated by their users and integrated into their practices. To this end, we rely on the situated cognition and situated acceptance approaches. Our study involves a subsidiary of a French energy group that has mandated a real-estate consulting firm to design and accompany their relocation to an activity-based environment. Our methodology is based on seven interviews and three days of observations carried out within their workspaces. Our results highlight not only the way in which the rules that ensure the smooth running of these work environments are understood and integrated into the situated practices of the actors, but also how these actors remodel and reconfigure these rules in order to make them relevant to their work. This study shows the importance of providing a more situated understanding of the use of activity-based workspaces and the way it transforms the actors' relationships with their own activity.